The Logic of Belief Persistency - Giacomo Bonanno; Pierpaolo Battigalli (University of California, Department of Economics, 1995)
The interaction bietween knowledge and belief in a temporal context is analyzed. An axiomatic formulation and semantic characterization of the principle of belief persistency implied by the standard conditionalization rule are provided. This principle says that an individual does not change her mind unless new evidence forces her to do so. It is shown that if beliefs are conscious (or stateindependent) and satisfy negative introspection then the principle of persistency of beliefs is characterized by the following axiom schema: the individual believes that 9 at date t if and orilly if she believes at date t that she will believe that 4 at date t+l.
Keywords: 330